PENERAPAN INTERNET OF THINGS (IOT) DALAM SISTEM OTOMATISASI PENGISIAN DEPOT AIR GALON - Rama Sampurna; Vera Veronica; Silfia Rifka (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
Manually filling gallons of water causes many problems, such as volume inaccuracy, waste, and suboptimal water quality monitoring. This research aims to develop an Internet of Things (IoT)-based gallon water filling automation system using an ESP32 microcontroller and a flow meter sensor for accurate water volume measurement and real-time monitoring via a web dashboard and WhatsApp notifications. The methods used include literature review, hardware and software design, and comprehensive system testing. This system integrates RFID-based user authentication, automatic pump and solenoid valve control, transaction data recording in a MySQL database, and automatic user notifications. Test results show that the system can automatically and accurately fill gallons of water to the desired volume, stop the flow when the gallon is full, minimize human error, and allow users to monitor the filling process remotely. Thus, this system provides a more efficient, modern, and transparent gallon water filling solution for drinking water depot businesses